Increased bleeding risk during percutaneous coronary interventions by arterial hypertension - Ndrepepa, Gjin; Groha, Philipp; Lahmann, Anna L.; Lohaus, Raphaela; Cassese, Salvatore; Schulz-Schuepke, Stefanie; Kufner, Sebastian; Mayer, Katharina; Bernlochner, Isabell; Byrne, Robert A.; Fusaro, Massimiliano; Laugwitz, Karl-Ludwig; et al. (Catheterization and Cardiovascular Interventions, 2016)
Objectives: We aimed to assess the association between arterial hypertension and bleeding in patients undergoing percutaneous coronary intervention (PCI). Background: The impact of arterial hypertension on bleeding risk of patients with coronary artery disease undergoing PCI is unknown. Methods: This study included 14,180 patients who underwent PCI. Bleeding was defined using the Bleeding Academic Research Consortium (BARC) criteria. Arterial hypertension was defined as treatment with antihypertensive drugs or a systolic blood pressure >140 mm Hg and/or diastolic blood pressure value >90 mm Hg documented on at least 2 occasions. The primary outcome was bleeding rate within 30 days of PCI. Results: Overall, 11,066 patients (78.0%) had arterial hypertension. Bleeding events occurred in 1,232 patients with arterial hypertension and 278 patients without arterial hypertension (11.1% vs 8.9%; odds ratio [OR] = 1.28, 95% confidence interval [CI] 1.11–1.46, P < 0.001). Access-site bleeding occurred in 730 patients with arterial hypertension and 175 patients without arterial hypertension (6.6% vs 5.6%: OR = 1.19 [1.01–1.41], P = 0.049). Non-access-site bleeding occurred in 502 patients with and 103 patients without arterial hypertension (4.5% vs 3.3%; OR = 1.39 [1.12–1.72], P = 0.003). After adjustment, arterial hypertension was significantly associated with any bleeding (adjusted OR = 1.41 [1.19–1.67], P < 0.001), access-site bleeding (adjusted OR = 1.36 [1.10–1.68], P = 0.005) and non-access-site bleeding (adjusted OR = 1.42 [1.09–1.83], P = 0.008). A history of arterial hypertension increased the risk of non-access-site bleeding (P = 0.002), whereas systolic blood pressure at the time of PCI increased the risk of access site bleeding (P = 0.018). Conclusions: Arterial hypertension is associated with increased risk of bleeding during PCI procedures. © 2015 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: arterial hypertension; bleeding; coronary artery disease; percutaneous coronary intervention